PERAN WORLD TRADE ORGANIZATION (WTO) DALAM MENYELESAIKAN SENGKETA PERDAGANGAN DAGING SAPI ANTARA AMERIKA-INDONESIA TAHUN 2012-2016 - Aditya Oktaviano; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is an international political economy study explaining the role of an international trade organization or rather an international trade regime better known as the world trade organization. The World Trade Organization (WTO) was officially established on January 1, 1995, the trading system itself has existed since 1948, the General Agreement on Tariffs and Trade (GATT). From 1948 to 1994 the GATT system contained regulations on world trade and resulted in the highest international trade growth. GATT as the organization and regulations produced are still temporary.The World Trade Organization (WTO) as an international trade regime is expected to bridge all the world's interests in the world in the trade sector through mutually agreed terms. The World Trade Organization (WTO) is proposed to produce mutually beneficial conditions so that all countries can benefit. The World Trade Organization (WTO) launched a model of trade where trade activities between countries are expected to run smoothly.This study uses the perspective of Neoliberalism which views that the state is not one of the actors who play a role in International Relations in international dispute settlement there are international organizations in the settlement. Neoliberalism is a theory in international relations that describes concepts of rationality, and contract, and focuses on the role of institutions and organizations in international politics. Neoliberalism reduces state intervention in the economy to be replaced by markets, and markets serve as one system for regulating the economy and at the same time the only benchmark for judging the success of government policy.Keywords : international political economy, World Trade Organization (WTO), General Agreement on Tariffs and Trade (GATT ), Neoliberalism, government policy